Respuesta :

For this case we must simplify the following expression:

[tex](1 + i \sqrt {12}) - (- 8 + i \sqrt {3})[/tex]

We apply distributive property to the terms of the second parenthesis considering that:

[tex]- * - = +\\- * + = -[/tex]

So:

[tex]1 + i \sqrt {12} + 8-i \sqrt {3} =[/tex]

Rewriting:

[tex]1 + i \sqrt {2 ^ 2 * 3} + 8-i \sqrt {3} =\\1 + 2i \sqrt {3} + 8-i \sqrt {3} =[/tex]

Adding similar terms:

[tex]1 + 8 + 2i \sqrt {3} -i \sqrt {3} =\\9 + i \sqrt {3}[/tex]

Answer:

[tex]9 + i \sqrt {3}[/tex]

ACCESS MORE